The Philippines’ Community-Based Resource Management Program - Osita, Willie (Annals of Tropical Research, 2003)
Community-Based Resource Management is a $US50M project financed by the World Bank and the Philippine government, designed to address the twin objectives of ameliorating rural poverty and resource degradation through support for locally generated and implemented natural resource management projects. The project aims to strengthen the capacity of local communities in forest, upland and near-shore areas, and that of Local Government Units (LGUs) to plan and implement investments for community-initiated development projects to reduce poverty and environmental degradation. Coordination is provided by the Department of Finance, with projects implemented through the LGUs. Loan and grant assistance are provided to LGUs, the balance of which depends on the financial class of the LGU applicant.